Tai-sabaki for the piano, tai-sabaki for the tatami – A tribute to Prof. em. David B. Waterhouse (1936-2017) (Revista de Artes Marciales Asiáticas, 2018)
David B. Waterhouse (1936-2017) was a Professor emeritus, Japanese studies scholar, and humanities polymath. Educated to concert pianist level, he graduated in Western Classics, Moral Sciences, and Oriental Studies from the University of Cambridge. It is there where during his freshman year he had attended for first time a live judo demonstration, and had decided to start his judo career. Professor Waterhouse would eventually join the University of Toronto, where he would spend the rest of his professional career as an educator and scholar. David aptly understood and taught judo as it was meant by its founder, i.e. as a form of pedagogy striving for both physical and intellectual development. Consequently, his academic judo classes at the University of Toronto’s Department of East Asian Studies attracted an enthusiastic crowd of students. Professor Waterhouse’s scholarly legacy is vast, showing a remarkable breadth in topics which he surveyed, investigated and mastered, but he was particularly proud of his magnum opus, i.e. a two-volume catalogue of woodcuts by Japanese artist Suzuki Harunobu published in 2013. The manuscript of his book on judo’s cultural and technical history, unfortunately, remains unfinished due to his untimely passing.